Takhalli In Tasauf - Artika; Riski Nurdilah; Rahmad Hidayah Pulungan; Febrian Alfarizi Siregar (Sufiya Research Institute, 2023)
Humans are created as creatures with flaws but have the potential to be perfect. By taking the path of Sufism to drink spiritual favors. Takhalli means empyting the heart and mind from things that can pollute such as heart disease or mental disorders that are still raging before doing worship. Lust is not a human who controls lust. That is why to enter the life of sufism one must be able to control his desires so as not to lead him astray.